Determining the Ability of the Vision, Aphasia, and Neglect (VAN) Stroke Scale to Identify Large Vessel Occlusion Strokes Within the Prehospital Setting: A Prospective Cohort Study - Lydia Leavitt (University Library System, University of Pittsburgh, 2022)
Background: One scale that has shown promise in identifying identify large vessel occlusions (LVOs) is the vision, aphasia, and neglect (VAN) scale. Our understanding of this scale's true performance, however, is limited as a majority of studies have been carried out in the hospital setting. The objective of this study is to evaluate the ability of the VAN scale to predict LVOs in the prehospital setting. Methods: Prospective cohort study comparing emergency medical service personnel administered VAN results to hospital discharge diagnoses to evaluate VAN's ability to predict a large vessel occlusion stroke. Main outcome measures included VAN sensitivity, specificity, positive and negative predictive values, positive and negative likelihood ratios, and accuracy.  Results: Emergency medical service personnel administered the VAN assessment to 185 patients suspected of having a stroke. VAN had a sensitivity of 0.81 (CI, 0.61 to 0.93), specificity 0.56 (CI, 0.48 to 0.64), positive predictive value 0.24 (CI, 0.61 to 0.34), negative predictive value 0.95 (CI, 0.87 to 0.98), positive likelihood ratio 1.87 (CI, 1.45 - 2.40), negative likelihood ratio 0.33 (CI, 0.15 - 0.73), and 60% accuracy (CI, 53% - 61%) for large vessel occlusion identification. Conclusion: When negative, VAN offers relatively high assurance that the patient is not suffering a large vessel occlusion stroke. However, VAN is non-specific for large vessel occlusions and results in many false positives. Therefore, pre-hospital decision-making regarding triage should not rely exclusively on VAN due to possible over-triage to facilities with endovascular capabilities.